A breath of not so fresh air…. Issue 3 (11th October 2022) - Pinto Pereira, João; Hantson, Philippe; Pieters, Thierry; Apraxine, Matveï; Froidure, Antoine
Despite being widely used as a recreational drug, "poppers" lack a legal framework for their delivery. Their composition may vary largely. This report describes a case of severe bronchiolitis following amyl nitrite mixture inhalation. https://bit.ly/3p3S7LM